2018
DOI: 10.3390/geosciences8010021
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Paleobathymetry of the Cenomanian–Turonian (94 Ma) Boundary Global Ocean

Abstract: At present, global paleoclimate simulations are prepared with bathtub-like, flat, featureless and steep walled ocean bathymetry, which is neither realistic nor suitable. In this article, we present the first enhanced version of a reconstructed paleobathymetry for Cenomanian-Turonian (94 Ma) time in a 0.1 • × 0.1 • resolution, that is both realistic and suitable for use in paleo-climate studies. This reconstruction is an extrapolation of a parameterized modern ocean bathymetry that combines simple geophysical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In some cases, the costs of data collection are not the only impediments to the production of DBMs, but our inability to travel through time may be: Goswami et al [25] presented an innovative approach to produce a DBM representing a reconstruction of paleobathymetry from 94 Ma, with implications for paleoclimate studies, among others. This new bathymetric model at 0.1 • × 0.1 • resolution improves upon present global paleoclimate simulation model layers that are developed from bathtub-like, flat, featureless ocean bathymetry models, which are neither realistic nor suitable.…”
Section: Generating a Digital Bathymetric Modelmentioning
confidence: 99%
“…In some cases, the costs of data collection are not the only impediments to the production of DBMs, but our inability to travel through time may be: Goswami et al [25] presented an innovative approach to produce a DBM representing a reconstruction of paleobathymetry from 94 Ma, with implications for paleoclimate studies, among others. This new bathymetric model at 0.1 • × 0.1 • resolution improves upon present global paleoclimate simulation model layers that are developed from bathtub-like, flat, featureless ocean bathymetry models, which are neither realistic nor suitable.…”
Section: Generating a Digital Bathymetric Modelmentioning
confidence: 99%
“…Tectonic and palaeogeographic studies of Upper Cretaceous rocks have previously suggested the existence of a seaway linking the Atlantic and Tethys Oceans during that timeframe (Scotese, 2014), with a link via the Trans-Sahara seaway purported to be active from the early Cenomanian to Maastrichtian (Scotese, 2014). Goswami et al (2018) presented a global bathymetry of the Cenomanian, which suggested a link between the two seas. Attempts to define the path taken by such a Trans-Sahara seaway have been hampered by poor stratigraphic control in the oldest marine deposits of the Benue Trough (Zaborski, 2000;Edegbai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%